2018
DOI: 10.18203/2349-3933.ijam20184718
|View full text |Cite
|
Sign up to set email alerts
|

Color doppler assessment of extra cranial carotid arteries in carotid artery disease with correlation of risk factors in predicting cerebro vascular accident in patients with carotid atheromatous disease

Abstract: Background: Stroke is a clinical syndrome, which describes a sudden neurological deficit of presumed vascular origin. The risk factors for stroke are diabetes mellitus, smoking, alcohol and hypertension. Colour doppler ultrasound is one of the important tool for the evaluation of exracranial insufficiency of the carotid arteries. This study was performed to assess the carotid arteries with the help of color doppler in carotid artery disease.Methods: Of the 100 patients who had come to our department during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 7 publications
6
7
1
Order By: Relevance
“…The present study is also in accordance with Noor ul hadi et al [10] , Bollipo JP [11] et al, SK Sethi et al [12] , and Fernandes et al [13] , all of which showed the most common age group to be involved being 61 -70 years. [12] Noor Ul Hadi (n = 100) 2009…”
Section: Ischemic Stroke -Demographics and Risk Factorssupporting
confidence: 92%
See 2 more Smart Citations
“…The present study is also in accordance with Noor ul hadi et al [10] , Bollipo JP [11] et al, SK Sethi et al [12] , and Fernandes et al [13] , all of which showed the most common age group to be involved being 61 -70 years. [12] Noor Ul Hadi (n = 100) 2009…”
Section: Ischemic Stroke -Demographics and Risk Factorssupporting
confidence: 92%
“…2 patients showed Complete carotid occlusion fulfilling the criteria laid down by Erickson SJ et al [33] 3 patients in the present study were found to have near total occlusion. (Graph 10) Laith Ahmed et al [14] Bollipo JP et al [11] The present study correlated with the Bollipo JP et al [11] where the predominant patients were the ones with mild stenosis. In the studies done by Laith Ahmed et al [14] and Noor Ul Hadi et al [10] majority of the patients belonged to the category of <50% stenosis (Table 15) AbuRahma et al [34] did a critical appraisal of the established criteria for the quantification of carotid stenosis by SRU consensus 27 .…”
Section: Degree Of Stenosis In Patients With Atherosclerotic Plaquesupporting
confidence: 85%
See 1 more Smart Citation
“…8,11,15 The common clinical presentation of the study patients was right sided hemiparesis (38.3%), left sided hemiparesis (34.2%), motor aphasia (21.7%), loss of consciousness (21.7%), TIA (17.5%) and facial deviation (17.5%). Hemiparesis (predominantly right sided) followed by aphasia and loss of consciousness were similarly the commonest manifestation by Pathak et al 8 , Fernandes et al 11 , and Bollipo et al 14 No abnormal findings were seen in 15% in brain neuroimaging. Lacunar infarcts (34.2%) were the most common findings followed by MCA infarct (30%), ACA infarct (10.8%) and posterior circulation infarct (10%).…”
Section: Discussionmentioning
confidence: 85%
“…However, maximum number of patients belonged to even younger age group of 51-60 years according to Haq et al1 3 About 7.5% were young stroke patients, aged <40 years in the current study. Even more, i.e., 12% patients were aged below 40 in the study by Bollipo et al 14 Conventional risk factors in the study participants were hypertension (80%), diabetes (62.5%), dyslipidemia (51.7%) and actively smoking (86.6%). These were the independent risk factors of ischemic stroke in previous published studies as well.…”
Section: Discussionmentioning
confidence: 87%